The effect of employee silence dimensions on affective commitment - Rizky Rahmatari Handayani; Haryadi Haryadi; Ratno Purnomo (Faculty of Economics and Business, Jenderal Soedirman University, 2017)
This research is a survey research at employees of KPP Pratama (Tax Service Office) Purwokerto branch. This study takes the title: